The Effect of Liquidity and Leverage on Firm Value Through Profitability at PT. Indofood Sukses Makmur Tbk - Ripaluddin Ripaluddin; Milka Pasulu; Ansar Taufiq (Jurnal Economic Resource, 2023)
The purpose of this study was to analyze and determine the effect of liquidity and leverage on firm value through profitability at PT. Indofood Sukses Makmur, Tbk. Quantitative research methods were processed using the Structural Aquation Modeling Partial Least Square(SEM-PLS) and Warp Pls 8.0 applications. Research population data from secondary data obtained from financial reports and annual reports per quarter I-IV on the Indonesia Stock Exchange for the period 2019-2021.  The results of this study indicate that liquidity and leverage have a positive and significant effect on firm profitability, but on firm value, the effect of liquidity and leverage is negative, while profitability has no significant effect on firm value.